A biomechanical analysis of the shot put performance - Sugumar, C. (Global journal for research analysis, 2014)
The aims of this study is to present a biomechanical over view of the performances of the men`s shot put at the Podichery and Tamilnadu state interphysical education meet held at Annamalai Univeristy, Chidambaram. To make the study feasible the video graphic technique was adopted. The video was observed on biomechanical parameters of shot put performance namely angle of release, arm angle at the time of release and velocity of release. The collected data were analysed with simple correlation. The analysis of the data indicates that shot put throwing performance was depends upon the angle of release and velocity of release.